Can honesty reminders reduce dishonesty in budgetary slack? - CHENG, Wilfred W. H. (Institutional Knowledge at Singapore Management University, 2023)
This study investigates the effect of honesty reminders on budgetary slack. Based on self-concept maintenance theory, the authors posit that honesty reminders can reduce budgetary slack by making people more aware of their own standards of honesty, resulting in more honest behavior. Using an experimental research design, the authors find evidence that honesty reminders reduce budgetary slack. The authors also find that although penalties can similarly reduce budgetary slack, they tend to cause distrust and resentment from subordinates. Therefore, honesty reminders may be a less costly method than penalties for reducing budgetary slack.